The reform of Chinese flower and bird painting from 1949 to 1966 - taking the "Beijing-Tianjin painting school" As an example - Gao Xue; Musnin Misdih (Akademi Seni dan Teknologi Kreatif, Universiti Malaysia Sabah, 2024)
This paper takes the development context and reasons of the reform of flower-and-bird painting from 1949 to 1966 as the starting point, applies iconography theory and Chinese traditional aesthetics theory, takes the works of representative painters of the "Beijing-Tianjin School of Painting" as the research object, and focuses on the changes in the style of flower-and-bird painting in the past 17 years in New China, and conducts graphic analysis from the subject matter of the works. In the past 17 years, the subject matter of flower-and-bird painting cannot be determined by itself. Its value is to serve the people's lives and emphasize the social function of art. The artistic function has been weakened and the cultural connotation has been ignored. This study found that in the development and evolution of flower-and-bird painting, it is necessary to objectively clarify the guidance of political thought on flower-and-bird painting, so that it can give full play to its own artistic advantages to serve the people, and also understand the way of integrating Chinese traditional thought with Western thought. Develop the art of flower-and-bird painting to the greatest extent.